Japanese micrologistic system Kamban as a means of communication in production system JIT - A. V. Kagalnikova (Vestnik MGIMO-Universiteta)
In the article the author researches the Kamban system as an important means of communication as part of logistic system «Just in Time»; touches the history of the system; explains the essence of the method, elucidating the main rules of its using and analyzes cardinal problems that can be faced by some enterprise during adoption of this method in their production.